INFLUENCE OF SOCIAL MEDIA ON ACADEMIC PERFORMANCE OF STUDENTS - MUNNA LAL (International Journal of Multidisciplinary Research and Studies, 2020)
Today, people all across the world are commemorating the advancements that have been made in communication technology, which have increased the breadth of communication made possible by information and communication technologies (ICTs). There is no doubt that advancements in technology in the field of communication have made the whole world into a "global village." The fact of the matter is, however, that technological advancements carry with them not just beneficial but also detrimental aspects. It assists people in becoming better informed, more enlightened, and current on the latest advancements taking place across the world. The advancement of technology has shown people more efficient ways to complete tasks. Twitter, Yahoo Messenger, Facebook Messenger, Blackberry Messenger (BBM), Whatsapp Messenger, 2go Messenger, Skype, Google Talk, Google Messenger, iPhones and Androids are all examples of social networking sites. Blackberry Messenger (BBM) is another example. The majority of individuals nowadays use social networking sites to keep up with old friends and make new ones, whether those relationships be in real life or online ( Asemah and Edegoh, 2012). The rapid development of technology has had a profound impact on the globe, and as a consequence, people are increasingly turning to various forms of technology as the most effective means by which to investigate a diverse range of topics. Because of the rapid development of internet technology, it is now widely recognised as the most effective channel for communication. As a result, approximately two-thirds of the population of the globe uses the internet to visit social networking or blogging sites, which serve as a tool for communication and interaction. Social networking sites, often known as SNSs, are online communities of people who use the internet and desire to engage with other people using the internet about topics that are of mutual interest, whether it be from a personal, professional, or intellectual point of view.